„Low Flame Management": New challenge to management theory and practice in Eastern Europe - Hoványi, Gábor (Marketing & Menedzsment, 2019)
There are typical crisis situations and already well known crisis management techniques. But a new type of crisis emerged in the economic transition of East-European countries: companies had to shut large production capacities because of the collapse of their traditional markets - but the remaining parts of the firms could operate without an imminent threat of bankruptcy. The management of a company possessing unused assets required a new technique: the "low flame management technique". This management practice has a special character as well as ominous consequences on the longer run - and offers also some lessons both for company management in general and for decision makers responsible for the economic policy of a country.